Association of apolipoprotein E gene polymorphisms with risk of coronary artery disease in a Han Chinese population at middle and high altitude in China - Zeng, Fanrong; Zhang, Xinyi; Zhang, Meng; Liu, Hongli; Li, Yuan; Ye, Fan; Chen, Xuejiao; Zhu, Fangyi; Zhai, Lihong (Frontiers in Endocrinology, 2026)
IntroductionThis study investigated the impact of APOE gene polymorphisms on the development of coronary artery disease (CAD) in the Han Chinese population at middle and high altitudes, focusing on lipid level regulation and atherosclerosis.MethodsThis retrospective case-control study involved 628 CAD patients and 628 matched controls without CAD. ApoE genotyping was conducted using PCR-chip technology, and genotype and allele frequencies were compared between groups. Multivariate logistic regression analyzed the link between ApoE polymorphisms and CAD risk in populations at middle and high altitudes.ResultsThe data revealed significant differences in APOE gene ε3ε4 and ε4ε4 genotypes, as well as ε4 allele frequencies, 1256 CAD and non-CAD cases (p < 0.05). CAD patients with the ε4 allele had higher Apo-B/Apo-A1, Apo-B, and LDL-C levels than those with the ε2 or ε3 alleles. Furthermore, multifactorial logistic regression analysis indicated that the APOE gene’s ε3ε4 genotype (OR = 1.514, 95% CI = 1.087 - 2.109, p = 0.014) is an independent predictor for CAD.DiscussionThese findings validated that the APOE gene’s ε3ε4 genotype is a potential predictor for CAD onset in Han Chinese individuals at middle and high altitudes.